An ultrasensitive electrochemical immunosensor based on C60-modified polyamidoamine dendrimers and Au NPs for co-catalytic silver deposition. (28th February 2018) - Chen, Peipei; Wang, Ting; Zheng, Xiangli; Tian, Dong; Xia, Fangquan; Zhou, Changli
Abstract : C60 -Modified polyamidoamine dendrimers and Au NPs for the co-catalytic deposition of silver, used for ultrasensitive electrochemical immunosensing. Abstract : A convenient, highly efficient and ultrasensitive electrochemical immunosensor was developed using in situ deposited silver nanoparticles (Ag NPs) as tracing tags for fetoprotein (AFP) detection. The function of the immunosensor was achieved by a co-catalytic effect on the surface of nanocomposites containing polyamidoamine (PAMAM) dendrimers coated with C60 (PAMAM-C60 NPs) and gold nanoparticles (Au NPs). On the surface of Au@PAMAM-C60 NPs labeled with an antibody (Ab2 ), via a sandwich-type immunoreaction, silver ions in solution were reduced to metallic Ag NPs. The electrochemical signal of the in situ deposited Ag NPs could be utilized to monitor the immunoreaction. Under optimum conditions, the peak current of the Ag NPs increased with increasing AFP concentration in the range from 0.1 pg mL −1 to 10 ng mL −1, with a detection limit of 0.03 pg mL −1 . Importantly, the designed electrochemical immunoassay strategy exhibited excellent sensitivity, stability, selectivity, and reproducibility.